INVESTIGATION OF THE GENETIC STRUCTURES AND PHYLOGENETIC RELATIONSHIPS FOR THE SPECIES OF THE GENUS ANTHRISCUS PERS. (APIACEAE) DISTRIBUTED IN TURKEY, USING THE NON - CODING TRN REGIONS OF THE CHLOROPLAST GENOME - Sancar, Pelin Yilmaz; Civelek, Semsettin; Tekin, Mehmet; Dastan, Sevgi Durna (Pakistan Botanical Soc, 2019)
The genus Anthriscus Pers. of the family Apiaceae is a small sized genus with 16 species, distributed in the world. In Turkey it is represented by 8 taxa, distributed in 4 sections. The aim of this study was to determine the genetic proximity and distances of taxa to each other and to identify interrelationships, systematic and phylogenetic relationships using the sequence analysis information of the non-coding trn region in the chloroplast genome of the Anthriscus species in Turkey. The phylogenetic tree showed that the taxa A. caucalis var. caucalis and A. tenerrima var. tenerrima (belonging to sect. Anthriscus) with A. cerefolium var. trichocarpa (belonging to sect. Cerefolium) had completed their speciations and isolation with other species in terms of speciation was provided. It can be said that A. kotschyi, the only representative of the sect. Caroides in Turkey, is isolated having completed its speciation also. The presence of the continuing gene exchange between the taxa can be mentioned, while the taxonomy of the two taxa of A. sylvestris and A. lamprocarpa, two members of the sect. Cacosciadium, cannot be determined more clearly yet. For this reason, it can be said that the A. sylvestris subsp. sylvestris and A. sylvestris subsp. nemorosa taxa, previously identified as two subspecies belonging to A. sylvestris, should be raised again to A. sylvestris and A. nemorosa taxa. In addition, an infrageneric arrangement and subsequent taxonomic regulation need to be made for the subspecies belonging to the A. lamprocarpa taxa.
Keywords: Apiaceae; Anthriscus; Chloroplast DNA; Molecular phylogeny; PCR; trnL3 '-trnF region